Fluid intake, hydration status and body mass changes in U-15 judo athletes during a training day - Bayram Ceylan; Luis Santos (Universidade Estadual de Maringá, 2022)
Despite numerous studies related to dehydration there is still a lack of scientific literature presenting hydration status and fluid intake of judo athletes during different periods. Therefore, the aim of this study was to investigate, fluid intake, hydration status and body weight changes of young judo athletes during a typical day of training in preparation period. Twenty-two young judo athletes (age: 12 ± 0.7 y, experience: 3.5 ± 1.1) voluntarily participated in this study. Hydration status and weight were examined in the morning, before and immediately after the training. All athletes trained 90 min and they consumed fluids ad libitum during the exercise. According to morning urine specific gravity (USG) values, 81.2% of the athletes were dehydrated while only 18.8% of the athletes were euhydrated. Pre-training urine measurements showed that 63.64% of the athletes presented dehydration and 77.27% of the athletes completed the training in dehydrated condition despite fluid availability during the training. Mean body weight loss during training was -0.64 ± 0.66%. It can be concluded that young judo athletes presented high prevalence of dehydration as indicated by USG values. Most of the athletes were dehydrated during a typical training day and completed the training in more dehydrated conditions compared to pre training values despite ad libitum fluid intake. It is of great importance to evaluate hydration status of the athletes before training to refrain from common practice of fluid restriction for weight loss and adverse effects of a persistent state of fluid deficit on physical and health related state.